2009
DOI: 10.1302/0301-620x.91b6.22319
|View full text |Cite
|
Sign up to set email alerts
|

The knee in full flexion

Abstract: There has been only one limited report dating from 1941 using dissection which has described the tibiofemoral joint between 120 degrees and 160 degrees of flexion despite the relevance of this arc to total knee replacement. We now provide a full description having examined one living and eight cadaver knees using MRI, dissection and previously published cryosections in one knee. In the range of flexion from 120 degrees to 160 degrees the flexion facet centre of the medial femoral condyle moves back 5 mm and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 13 publications
1
30
1
Order By: Relevance
“…Interestingly, the results of the present study also found increased contact strains in the lateral compartment at 105° of flexion. Since the medial meniscus is believed to have an important role in transmitting load in higher flexion angles (Lee et al, 2006; Pinskerova et al, 2009; Seitz et al, 2011; Yao et al, 2008), it is likely that disruptions in the position of the knee due to a medial meniscus tear alter load transmission through the lateral compartment as well, as observed in this study.…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, the results of the present study also found increased contact strains in the lateral compartment at 105° of flexion. Since the medial meniscus is believed to have an important role in transmitting load in higher flexion angles (Lee et al, 2006; Pinskerova et al, 2009; Seitz et al, 2011; Yao et al, 2008), it is likely that disruptions in the position of the knee due to a medial meniscus tear alter load transmission through the lateral compartment as well, as observed in this study.…”
Section: Discussionmentioning
confidence: 64%
“…First, the posterior part of the lateral femoral condyle was posteriorly displaced. During deep flexion kneeling, the posterior surface of the tibia and posterior aspect of the femoral condyle are in direct contact [6]. Thus, a malunited femoral condyle may prevent hyperflexion.…”
Section: Discussionmentioning
confidence: 99%
“…These features were intended to provide stability to the TKA throughout the whole range of flexion [4]. The lateral condylar design was a single 24 mm anteroposterior radius design, with a matching concavity in the lateral side of the polyethylene insert intended to tolerate some rotation around the medial sphere and thereby conform to the reported kinematics of the natural knee [5]- [8].…”
Section: Methodsmentioning
confidence: 99%